REMARKABLE ENHANCEMENT OF MEAN PLATELET VOLUME IN IRANIAN PATIENTS WITH TYPE 2 DIABETES MELLITUS WITH NO DEPENDENCE ON HEMOGLOBIN A1C LEVEL (Iraqi Journal of Medical Sciences, 2018)
Background: Diabetes mellitus (DM) is a pandemic disease that leads to several complications. Platelet reactivity plays a major role in diabetes complications. Mean platelet volume (MPV) is a marker of platelet size that is easily determined on routine automated blood counters. Studies have been found that MPV is enhanced in patients with DM.Objective: To assess any relationship between MPV in type 2 Diabetic persons and with glycohemoglobin (HbA1c) level.Methods: The study included a total of 130 subjects who were referred to Samenol Aemme and Mehregan hospitals in Mashhad city, Iran, between April 2013 and November 2014 for a routine check-up. All subjects were divided into two groups as following: Patients with type 2 diabetes group, which comprises 63 subjects and non-diabetic control group, which comprises 57 individuals. Blood sample from each individual was collected after a 12-hour overnight fasting. MPV, HbA1c and fasting blood sugar (FBS) were also monitored. Results: MPV values were found to be 8.7±0.36 fl (p
Keywords: Platelet reactivity; HbA1c measurement; diabetic patients